Evaluasi Ex-Ante Dokumen Rencana Peningkatan Kepatuhan Wajib Pajak Tahun 2024 Milik Direktorat Jenderal Pajak - Al-Firdaus, Farid (Polytechnic of State Finance STAN, 2024)
The Indonesian Directorate General of Taxes (DGT) mitigates the risks that challenge the taxpayers' voluntary compliance through the 2024 compliance improvement plan (CIP). The author evaluates it before it is implemented (ex-ante) by assessing its objectives, regulatory compliance, stakeholders' concerns, risks, strategy alternatives, and feasibility. The author documents that the CIP not only passes those assessments but also the phase of review by the stakeholders. On the other hand, the author found that the CIP is not based on the new risk management regulation ruling compliance and organizational risks that can help DGT cope with compliance risks and others, such as stakeholder resistance, political risks, and unforeseen consequences.